The Role of the Designer in the Organization of Preschool Education System Based on Modern Requirements - Nosirova Madina Mo'minovna (Genius Journals, 2022)
This article discusses the modern requirements of the system of preschool education based on the rolan his body in a stylist
Keywords: The value of universal and spiritual; leadership; progressive,